Articulatory reflexes of the three-way contrast in labial stops and kinematic evidence for domain-initial strengthening in Korean. (19th February 2016) - Cho, Taehong; Son, Minjung; Kim, Sahyang
Abstract : This study examines articulatory characteristics of the three-way contrast in labial stops /p p h p */ (lenis, aspirated, fortis, respectively) in Korean in phrase-initial and phrase-medial prosodic positions with a two-fold goal. First, it investigates supralaryngeal articulatory reflexes of the stops and explores articulatory invariance of these stops across prosodic positions. Second, it investigates Korean stops in kinematic terms from the perspective of domain-initial strengthening, and explores the nature of prosodically-conditioned speech production from a dynamical perspective. Results showed that the articulatory reflex of the three-way contrast was invariantly observed across prosodic positions with lip constriction degree (/p /</p h /</p */), while lip constriction duration showed a binary distinction (/p /</p h p */). Kinematically, there was only very weak articulatory evidence for the contrast across prosodic positions: The V-to-C lipclosing movement tended to be faster for /p h / than for /p /, and the C-to-V lipopening movement tended to be larger for /p h p */ than for /p /. As for domain-initial strengthening, the consonantal lip closing gesture was characterized by a larger, longer and slower articulation, whereas the vocalic lip opening gesture (after the release) was larger and faster, but not longer. Kinematic relations indicated that the lip closing movement is most likely controlled by a rate of the clock (possibly modulated by a temporal modulation gesture, or π-gesture) comparable to boundary effects in English, but the boundary-induced lip opening movement was better accounted for by a change in target (possibly modulated by a spatial modulation gesture, or μ-gesture) which was comparable to prominence rather than boundary effects in English. The cross-linguistic difference was interpreted as coming from different prosodic systems between Korean and English, presumably instantiated in dynamical terms of how the temporal and the spatial modulation gestures are phased with constriction gestures in relation to boundary marking versus prominence marking.